Nerve growth factor level in urine: opportunitiesa new diagnostic test in women with overactive bladder (findings) - F N Mahmedjanova; I A Apolikhina (IP Berlin A.V., 2013)
The reasons that cause the symptoms of overactive bladder, it is extremely diverse, so it is very important the correct diagnosis. Can the definition of nerve growth factor in the urine samples to be objective method of diagnosis of overactive bladder? In this article published by the original values of nerve growth factor in the urine samples of patients with overactive bladder and the control group.